A combination of temsirolimus, an allosteric mTOR inhibitor, with clofarabine as a new therapeutic option for patients with acute myeloid leukemia - Chiarini, Francesca; Lonetti, Annalisa; Teti, Gabriella; Orsini, Ester; Bressanin, Daniela; Cappellini, Alessandra; Ricci, Francesca; Tazzari, Pier Luigi; Ognibene, Andrea; Falconi, Mirella; Pagliaro, Pasqualepaolo; Iacobucci, Ilaria; et al. (My University, 2012)
Signaling through the phosphatidylinositol 3-kinase (PI3K) pathway and its downstream effectors, Akt and mechanistic target of rapamycin (mTOR), is aberrantly activated in acute myeloid leukemia (AML) patients, where it contributes to leukemic cell proliferation, survival, and drug-resistance. Thus, inhibiting mTOR signaling in AML blasts could enhance their sensitivity to cytotoxic agents. Preclinical data also suggest that allosteric mTOR inhibition with rapamycin impaired leukemia initiating cells (LICs) function. In this study, we assessed the therapeutic potential of a combination consisting of temsirolimus [an allosteric mTOR complex 1 (mTORC1) inhibitor] with clofarabine, a nucleoside analogue with potent inhibitory effects on both ribonucleotide reductase and DNA polymerase. The drug combination (CLO-TOR) displayed synergistic cytotoxic effects against a panel of AML cell lines and primary cells from AML patients. Treatment with CLO-TOR induced a G0/G1-phase cell cycle arrest, apoptosis, and autophagy. CLO-TOR was pro-apoptotic in an AML patient blast subset (CD34+/CD38−/CD123+), which is enriched in putative leukemia initiating cells (LICs). In summary, the CLO-TOR combination could represent a novel valuable treatment for AML patients, also in light of its efficacy against LICs.
Keywords: AML; PI3K/Akt/mTOR signaling; apoptosis; autophagy; combination therapy; leukemia initiating cells